O design de material didático e o processo de tradução/interpretação (Libras/Português): uma aproximação possível - Saito, Daniela Satomi; Scolari, Sérgio Henrique Prado; Felício, Márcia Dilma (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2011: Proceedings of the 17th Brazilian Symposium on Multimedia and the Web, 2011)
There is a gap concerning the production of courseware for deaf students. The objective of this article was through a case study; identify the moments and the approach in translation/interpretation process with the courseware design by the deaf students. The results revealed how complex is the translation/interpretation process, highlighting the necessity to define specific moments to work with the specificities of the program, leading to a deeper observation about accessibility of digital content.